Unveiling the role of carbon black in printable mesoscopic perovskite solar cells - Kajal, Priyanka (2022)
Carbon-based perovskite solar cells (C–PSCs) have attracted significant attention from the scientific community owing to their improved stability, low-cost fabrication, and potential scalability with screen printing technology. In this study, we examine the effect of three most commonly used carbon blacks, i.e. vulcan carbon (VC), meso carbon (MC) and super P (SP), on the properties of the resultant carbon electrode and the effect on photovoltaic performance as well as device stability. It shows that VC based carbon electrode promotes decent wettability to perovskite precursor solution, excellent infiltration and strong adhesion within the device stacks due to its high porosity and high pore volume. Furthermore, counter electrodes consisting of highly conductive VC exhibit sheet resistance of as low as 11.0 Ohm/□ as compared to those of MC (15.3 Ohm/□) and SP (22.0 Ohm/□). C–PSCs fabricated using VC based carbon electrode display champion power conversion efficiency of 12.55% with almost no decrease in efficiency under ambient conditions (~75% relative humidity) for 30 days without encapsulation. This work highlights the importance of carbon paste formulation for developing highly efficient and stable perovskite solar cells.